Strategies for Sustainable Employee Performance in the Post-Pandemic Era: A Qualitative Approach - Anastasia D’Ornay; Saripah A.RM; Ulfa Natsir (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The COVID-19 pandemic has fundamentally changed workplace dynamics, placing employee mental health and well-being at the forefront of Human Resource Management (HRM) priorities. As organizations navigate the post-pandemic era, ensuring continued employee performance requires a strategic emphasis on psychological resilience, work-life balance, and organizational support systems. This study uses a Systematic Literature Review (SLR) approach following the PRISMA framework to identify effective HRM strategies that promote workplace mental health and well-being. The study’s findings highlight key strategies, including flexible work arrangements, Employee Assistance Programs (EAPs), leadership-driven well-being initiatives, and the promotion of a supportive organizational culture. These strategies not only reduce mental health risks but also improve employee engagement, productivity, and retention. This study presents a comprehensive framework for HR practitioners to integrate well-being into organizational policies, ensuring long-term resilience and competitiveness in an increasingly volatile work environment.